Ultrasound cases of an elongated left lobe of the liver as an anatomical variant - N. V. Ischenko; N. K. Vinogradova; L. A. Titova; E. M. Tolstykh; S. I. Marks (Исследования и практика в медицине, 2024)
The elongated left lobe of the liver (saddle liver, saber liver, beaver tail liver, beaver lobe) is one of the types of variant liver anatomy, characterized by the fact that the left lobe extends far beyond the midline of the body, and can come into contact with the spleen and even go above it. Due to the fact that the elongated left lobe of the liver is more often susceptible to injury and, in some cases, can imitate a subcapsular hematoma of the spleen, it seems important to increase the awareness among doctors of various specialties about the variety of morphological variations in the structure of the liver, in particular about the elongated left lobe of the liver, to unify approaches to the description and establish uniformity of wording to designate this feature of the anatomical structure of the left lobe of the liver, which will reduce the risk of diagnostic errors and errors during surgical interventions, especially in cases of blunt abdominal trauma.The article presents clinical cases with ultrasound examination of 10 patients of different ages (from 1 month to 38 years) and gender with a newly diagnosed anomaly in the structure of the left lobe of the liver, i.e an elongated left lobe. An analysis of national and foreign literature sources containing reports on various morphological variants of the liver structure and the frequency of their occurrence was carried out. Ultrasound signs were proposed to describe the elongated left lobe of the liver. The features of the ultrasound examination technique for the elongated left lobe of the liver in children older than one year are described. The variety of formulations used by different authors when describing this variant of the anatomical structure of the liver was studied.